A systematic literature review of the risk factors associated with children entering public care. Issue 5 (5th December 2012) - Simkiss, D. E.; Stallard, N.; Thorogood, M.
Abstract Children who enter public care are among the most vulnerable in society. In addition to services for their medical needs, a focus on identifying and intervening with families in need where children are at high risk of entering public care is a public health priority. This paper aims to identify the characteristics of children, their parents or their social circumstances which are associated with children entering public care. The databases searched were CSA Illumina, British Education Index, ChildData, CINAHL, Excerpta Medica, MEDLINE, the Campbell and Cochrane Collaborations, NHS Centre for Reviews and Dissemination, NHS Evidence, Social Care Online and TRIP; from start dates to 7 February 2011. A total of 6417 titles were reviewed. After review, 10 papers with cohort or case–control methodologies met the inclusion criteria and the included papers were appraised using questions from the Critical Appraisal Skills Programme to guide the critique of case–control and cohort studies. A narrative synthesis is used to describe the research identified. Socio‐economic status, maternal age at birth, health risk factors and other factors including learning difficulties, membership of an ethnic minority group and single parenthood are described as risk factors associated with children entering public care. Health risk factors have been explored using databases developed for other purposes such as health insurance or hospital discharge. A number of risk factors for children entering public care are identified from the literature, some were culturally specific and may not generalize. The interaction between different risk factors needs testing in longitudinal data sets.